2009
DOI: 10.1038/jid.2009.124
|View full text |Cite
|
Sign up to set email alerts
|

Short-Sequence Oligopeptides with Inhibitory Activity against Mushroom and Human Tyrosinase

Abstract: Cutaneous hyperpigmentation is a common disorder due to excess melanin production by the enzyme tyrosinase. The gold standard for treatment is hydroquinone (HQ), which reduces pigmentation through its toxicity to melanocytes rather than via tyrosinase inhibition. We screened an internal library for oligopeptides that inhibited both mushroom and human tyrosinase but showed no cytotoxicity to human melanocytes. We identified two highly active inhibitory sequences, P3 and P4, of 8- and 10-amino-acid-length, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 41 publications
(37 reference statements)
2
61
1
Order By: Relevance
“…Thus, several studies made efforts to find novel proteins and peptides from natural resources, such as silk (Kato et al, 1998), milk (Nakajima et al, 1996;Chen et al, 2006), honey (Oszmianski, 1990;Ates and Cokmus, 2001), wheat (Okot-Kotber et al, 2001), and the housefly (Daquinag et al, 1995(Daquinag et al, , 1999, for tyrosinase inhibition. On top of that, dipeptides (Girelli et al, 2004), kojic acid tripeptides (Noh et al, 2007), mimosine tetrapeptides (Upadhyay et al, 2011), cyclic peptides (Morita et al, 1994), short-sequence oligopeptides (Abu Ubeid et al, 2009), and octameric peptides (Schurink et al, 2007) were also investigated for their tyrosinase-inhibitory abilities. Herein without precedent, we systematically and comprehensively investigated C-and N-terminal cysteine/tyrosine-containing tetrapeptides for tyrosinase inhibition and found that the CRVI tetrapeptide showed the strongest mushroom tyrosinase-inhibitory potency.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several studies made efforts to find novel proteins and peptides from natural resources, such as silk (Kato et al, 1998), milk (Nakajima et al, 1996;Chen et al, 2006), honey (Oszmianski, 1990;Ates and Cokmus, 2001), wheat (Okot-Kotber et al, 2001), and the housefly (Daquinag et al, 1995(Daquinag et al, , 1999, for tyrosinase inhibition. On top of that, dipeptides (Girelli et al, 2004), kojic acid tripeptides (Noh et al, 2007), mimosine tetrapeptides (Upadhyay et al, 2011), cyclic peptides (Morita et al, 1994), short-sequence oligopeptides (Abu Ubeid et al, 2009), and octameric peptides (Schurink et al, 2007) were also investigated for their tyrosinase-inhibitory abilities. Herein without precedent, we systematically and comprehensively investigated C-and N-terminal cysteine/tyrosine-containing tetrapeptides for tyrosinase inhibition and found that the CRVI tetrapeptide showed the strongest mushroom tyrosinase-inhibitory potency.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, continual efforts have been exerted to obtain tyrosinase inhibitors synthetically (in laboratories) 24−26 and naturally (through plant extractions). 27−29 Recently, we used phage-displayed tetrapeptide inhibitors 30 and a T1 compound from Gastrodia elata, 31 and other researchers have employed peptide-derived compounds for tyrosinase inhibition. 4,32,33 Certain short-sequence oligopeptides, P3 and P4, inhibit mushroom tyrosinase with no cytotoxicity to human melanocyte.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The aim was to produce oligopeptides with high tyrosinase inhibiting activity, that are neither cytotoxic nor mutagenic A number of peptide fragments have been shown to reduce pigment production [42][43][44].…”
Section: Other Botanicals As Potential Bleaching Agentsmentioning
confidence: 99%